2017
DOI: 10.1002/14651858.cd010651.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Surgical versus non-surgical management for pleural empyema

Abstract: Surgical versus non-surgical management for pleural empyema (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(102 citation statements)
references
References 48 publications
3
88
0
1
Order By: Relevance
“…Antibiotic treatment, chest drainage, intrapleural cavity injection, thoracoscopy, operation and nutrition support can be selective methods. Taking these patients as the center, summarize patient information and conduct comprehensive analysis to provide support for clinical decisions (68) and finding patients with potentially poor prognosis at the early stage in the future. At present, there have been studies on independent predictive factors, such as white blood cell count, pleural pain, pleural effusion position and pleural rupture for operative treatment (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibiotic treatment, chest drainage, intrapleural cavity injection, thoracoscopy, operation and nutrition support can be selective methods. Taking these patients as the center, summarize patient information and conduct comprehensive analysis to provide support for clinical decisions (68) and finding patients with potentially poor prognosis at the early stage in the future. At present, there have been studies on independent predictive factors, such as white blood cell count, pleural pain, pleural effusion position and pleural rupture for operative treatment (12).…”
Section: Discussionmentioning
confidence: 99%
“…In Korea, a study suggested that VATS can be a first-line treatment of pleural cavity infection (64). Some studies also consider that death rate does not have a significant difference between thoracoscopic surgery and conservative medical treatment (2,68), and have some contradictory results for the study and comparison between children VATS and medical treatment (2,65,66,69). Furthermore, there is a lack of high-quality, random and controlled clinical studies on VATS/medical treatment.…”
Section: Operationmentioning
confidence: 99%
“…The question remains as to whether VATS at initial presentation is superior to medical treatment. A recent Cochrane review suggested that there is no statistically significant difference in mortality between primary surgical and non surgical management of pleural empyema for all age groups . However, there was insufficient evidence to assess the impact of fibrinolytic therapy.…”
Section: Treatmentmentioning
confidence: 99%
“…A pleural empyema is defined as pus in the pleural space, most often secondary to pneumonia, though other aetiologies include trauma and iatrogenic 1. A spinal epidural abscess is defined as a collection of pus in the epidural space, which is a surgical emergency, as prolonged compression of the spine may lead to irreversible damage 2.…”
Section: Discussionmentioning
confidence: 99%